Exploring contribution of climate and population scenarios for southwest Germany on heat exposure of the elderly population - Nils Riach; Rüdiger Glaser; Andreas Matzarakis (Environment International)
Given that Europe is the continent with the fastest rate of warming which is additionally characterized by an aging population, an increase in urbanization and the prevalence of chronic diseases, it is of great importance to address the associated health risks posed by heat. Future demographic pathways present a significant challenge in risk research, especially in heat-health analyses, where many studies emphasize rising temperatures from climate change while often underestimating the role of population shifts that affect exposure and vulnerability, especially on the regional scale.We investigate the contribution of climate (RCP) and population (SSP) scenarios on heat exposure of the elderly population (60+) at a regional scale (1 km × 1 km) in Southwest Germany. Exposure is calculated in person-days by multiplying the elderly population under five scenario assumptions with each of the three heat metrics (TNge20, TXge30, WSDI) under three scenario assumptions. This approach enables us to assess and compare the contribution of each metric to the overall exposure. By 2090, heat exposure among the elderly is expected to rise significantly across all RCP-SSP combinations compared to 2010, with increases ranging from 175 % (TXge30 RCP2.6-SSP4) to 12,395 % (TNge20 RCP8.5-SSP5), and the proportion of elderly exposed in urban versus rural areas varying from 11 %/89 % (WSDI RCP4.5-SSP3) to 67 %/33 % (TNge20 RCP4.5-SSP5). Although uncertainties are inherently high, incorporating societal scenarios in regional and local heat risk assessments still provides valuable insights. Despite their limitations, demographic scenarios offer a foundation for understanding future vulnerabilities and guiding adaptation strategies. Further research is required to address adaptation beyond large urban areas, differentiating strategies and capacities for urban and rural settings.